Exploring Evolutionary and Transmission Dynamics of HIV Epidemic in Serbia: Bridging Socio-Demographic With Phylogenetic Approach - Jovanović, Luka; Šiljić, Marina; Ćirković, Valentina; Salemović, Dubravka; Pešić-Pavlović, Ivana; Todorović, Marija; Ranin, Jovan; Jevtović, Djordje; Stanojević, Maja (Frontiers in Microbiology, 2019)
Previous molecular studies of Serbian HIV epidemic identified the dominance of subtype B and presence of clusters related HIV-1 transmission, in particular among men who have sex with men (MSM). In order to get deeper understanding of the complexities of HIV subepidemics in Serbia, epidemic trends, temporal origin and phylodinamic characteristics in general population and subpopulations were analyzed by means of mathematical modeling, phylogenetic analysis and latent class analysis (LCA). Fitting of the logistic curve of trends for cumulative annual number of new HIV cases in 1984-2016, in general population and MSMs was performed. Both datasets fitted the logistic growth model, showing early exponential phase of the growth curve. According to the suggested model, by the year 2030 the number of newly diagnosed HIV cases in Serbia will continue to grow, in particular in the MSMs. Further, detailed phylogenetic analysis was performed on 385 sequences from the period 1997-2015. Identification of transmission clusters, estimation of population growth (Ne), of the effective reproductive number (Re) and time of the most recent common ancestor (tMRCA) was estimated employing Bayesian and Maximum likelihood methods. Substantial proportion of 53% of subtype B sequences was found within transmission clusters/network. Phylodynamic analysis revealed Re over one during the whole investigated period, with the steepest slopes and a recent tMRCA for MSM subtype B clades, in line with a growing trend in the number of transmissions in years approaching the end of the study period. Contrary, heterosexual clades in both studied subtypes – B and C, showed modest growth and stagnation. LCA analysis identified five latent classes, with transmission clusters dominantly present in 2/5 classes, linked to MSMs living in the capital city and with high prevalence of coinfection with HBV and/or other STIs. Presented findings imply that HIV epidemic in Serbia is still in the exponential growth phase, in particular related to the MSM transmission, with estimated steep growing curve until 2030. The obtained results imply that an average new HIV patient in Serbia is a young man with concomitant sexually transmitted infection.